PERAN PELAKSANA PENYULUHAN HUKUM KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM BANTEN DALAM SOSIALISASI UNDANG-UNDANG NO. 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Ratu Mimi Darniasih; Anton Aulawi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2020)
This research is motivated by my interest in the problem of the persistence of the phenomenon of forced withdrawal of installment vehicles in the City and Regency of Serang. based on observations in the Pasir Masjid Kampung Gembor Village, Binuang Subdistrict, Serang District, through an interview with Mr. Topik, a resident of Kampung Pasir Masjid who bought a vehicle on credit through a consumer finance institution and experienced defaults but at the time of being withdrawn byThe consumer finance institution, Mr Topik, can retain its graceful items because without proper procedures. the purpose of this research is to find out, understand and examine the role and obstacles of implementing legal counsel in Banten Regional Office of the Ministry of Law and Human Rights in the socialization of Law No.42 of 1999 concerning Fiduciary Guarantees to increase legal awareness. The research method used is descriptive method with a qualitative approach. the results of this study indicate the existence of (1) the role of implementing legal counseling in the Regional Office of the Ministry of Law and Human Rights of Banten having carried out their role as legal counselors by providing counseling both directly and indirectly and through collaboration with relevant agencies. specifically in Kampung Pasir Masjid in collaboration with LBH KKPMP. (2) Constraints faced include factors in the area; limited budget; HR in Kemenkumham is limited; legal counseling material is not just about fiduciary, and many people are still laymen regarding fiduciary law.